Face-to-Face, Online or Hybrid, Which Model is Preferred by University Students And Why? - Nükhet HOTAR; Mehmet Ali ÖZCAN; Bahar BARAN; Emre KARAGÖZ; Lütfiye Özge GÜNEY (Journal of Learning and Teaching in Digital Age, 2023)
Teaching model preferences of current university students and the factors explaining them indicate educators and decision makers how to design future higher education system. The literatüre indicates the importance of teaching, social and cognitive presence, gender and experience for sustainability of online environments. Therefore, this study aims to examine to what degree university students' experiences and opinions affect their teaching model preferences (face-to-face, online, hybrid). 5504 university students participated to the study and the data were collected by an online questionnaire. gender, opinions about the complexity of the learning management system, the sufficiency of digital materials, knowing how to solve problems during online learning, course participation preferences, online teaching methods (synchronous, asynchronous, both) preferences and teaching, social and cognitive presence levels are the factors of the study. Two-way contingency table analyses using Pearson χ^2 and multinomial logistic regression model (MLR) were applied to determine the factors affecting the teaching model preferences. The results indicated that 71.2 prefered online supported methods (online, hybrid) while only 25.8% preferred wholly face to face methods. Interestingly, more than half of the females preferred face-to-face and hybrid, while more than half of the males preferred online education. the teaching preferences of the students are dependent of the determined variables and Community of Inquiry elements that addressed in this study.